2013
DOI: 10.1186/1472-6882-13-46
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin induces cell cycle arrest and apoptosis in human KB cancer cells

Abstract: BackgroundCapsaicin, a pungent phytochemical in a variety of red peppers of the genus Capsicum, has shown an anti-proliferative effect on various human cancer cell lines. In contrast, capsaicin has also been considered to promote the growth of cancer cells. Thus, the effects of capsaicin on various cell types need to be explored. The anti-proliferative effects of capsaicin on human KB cancer cells are still unknown. Therefore, we examined the viability, cell cycle progression, and factors associated with apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 37 publications
7
69
0
Order By: Relevance
“…Lin CH et al, (2013) found that treatment of KB cells with capsaicin significantly reduced cell proliferation/ viability and induced cell death in a dosedependent manner. Cell cycle analysis indicated that exposure of KB cells to capsaicin resulted in cell cycle arrest at G2/M phase 43 . Capsicum was also reported to be effective against gastric cancer by inducing apoptosis and modulates MAPK signaling [44][45] .…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Lin CH et al, (2013) found that treatment of KB cells with capsaicin significantly reduced cell proliferation/ viability and induced cell death in a dosedependent manner. Cell cycle analysis indicated that exposure of KB cells to capsaicin resulted in cell cycle arrest at G2/M phase 43 . Capsicum was also reported to be effective against gastric cancer by inducing apoptosis and modulates MAPK signaling [44][45] .…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…It also enhances apoptotic effects by activating the calciumCaMKII-Sp1 pathway on Hep3B cell lines 38 . Human nasopharyngeal carcinoma was recovered by capsicum studied on NPC-TW 039 cell lines by inducing G0/G1 phase arrest, apoptosis and increased cytosolic Ca2+ level 43 . Lin CH et al, (2013) found that treatment of KB cells with capsaicin significantly reduced cell proliferation/ viability and induced cell death in a dosedependent manner.…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Capsaicin inhibited the growth of several cancer cells via induction of both apoptosis (Lin et al, 2013;Jin et al, 2014) and autophagy (Oh and Lim, 2009;Choi et al, 2010b). However, cancer cell death via apoptosis induction is more preferable in cancer therapy due to the cytoprotective role of autophagy (Vazquez-Martin et al, 2009;Dalby et al, 2010).…”
Section: Effect Of Hydroxycapsaicin On Apoptosis Induction In Human Cmentioning
confidence: 99%
“…The ROS have been shown to disrupt the mitochondrial membrane and induce apoptosis pathways in pancreatic cancer cells (Zhang et al, 2008). Capsaicin triggered the apoptosis pathway in human KB cancer cells (derived from HeLa cell line) by agitating the membrane potential of mitochondria and subsequently activating the caspase signaling pathway (Lin et al, 2013). However, capsaicin could also inhibit NF-ĸB (nuclear factor kappa-light-chain-enhancer of activated B cells) pathway which can cause apoptosis and minimize carcinogenic effects (Han et al, 2001;Patel et al, 2002).…”
Section: Anticancer Activitymentioning
confidence: 99%